THE CORRELATION BETWEEN WORK DISCIPLINE AND COMPETENCE IN TEACHER PROFESSIONALISM AT SMK NEGERI 1 TANJUNG LAGO - LIA MARDIATI; SUPARDI US (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The issue of education is a complex matter as it involves the family, school, and society. The government implements the National Education System in accordance with Law No. 2 of 1989 and No. 20 of 2003. National education aims to enrich the nation's life and shape the character of children to be devout, morally upright, and knowledgeable individuals. One component within the education system is the process of education. To achieve favorable educational outcomes, it is essential to have a well-structured and directed educational process. Such a process can only be carried out effectively by dedicated education professionals or teachers who are genuinely proficient in their field. Teachers, who are the primary key to improving the quality of education, must be dependable professionals. Therefore, the quality of a teacher influences students' learning achievements. However, there are still several challenges encountered in the field, such as a lack of work discipline and insufficient teacher competence. This research aims to analyze these factors and their correlation in teacher professionalism at SMK Negeri 1 Tanjung Lago. The findings of this study are expected to provide a better understanding of the correlation between work discipline, competence, and teacher professionalism. Additionally, it will offer recommendations and steps to enhance the quality of education in the school. ABSTRAKMasalah pendidikan merupakan masalah yang kompleks karena melibatkan keluarga, sekolah, dan masyarakat. Pemerintah menjalankan Sistem Pendidikan Nasional sesuai Undang-Undang No. 2 tahun 1989 dan No. 20 tahun 2003. Pendidikan nasional bertujuan mencerdaskan kehidupan bangsa dan membentuk watak anak yang beriman, berakhlak mulia, dan berilmu. Salah satu komponen yang ada di dalam sistem pendidikan adalah proses pendidikan. Untuk mencapai hasil pendidikan yang baik harus melalui proses pendidikan yang baik dan terarah. Pendidikan yang baik dan terarah hanya mungkin dapat dilaksanakan oleh tenaga kependidikan atau guru yang benar-benar profesional di bidangnya. Guru yang merupakan kunci utama dalam meningkatkan mutu pendidikan harus menjadi profesional yang dapat diandalkan. Oleh karena itu kualitas seorang guru mempengaruhi prestasi belajar siswa. Namun masih terdapat beberapa kendala seperti kurangnya disiplin kerja dan kurangnya kompetensi guru yang ditemui di lapangan. Penelitian dimaksudkan untuk menganalisis faktor-faktor tersebut dan hubungannya dengan tingkat profesionalisme guru di SMK Negeri 1 Tanjung Lago. Hasil penelitian ini diharapkan dapat memberikan pemahaman yang lebih baik tentang hubungan antara disiplin kerja dan kompetensi, dengan profesionalisme guru, serta memberikan rekomendasi dan langkah-langkah untuk meningkatkan kualitas pendidikan di sekolah.